Krokot Extract (Portulaca Oleracea. L) as Natural Light-harvesting pigments for Dye-Sensitized Solar Cells (DSSCs) : Influence of Dye Acidity - Cici Nurfaizah; Didik Krisdiyanto; Khamidinal Khamidinal; Sudarlin Sudarlin (Biology, Medicine, & Natural Product Chemistry, 2015)
Dye-sensitized solar cells (DSSCs) was fabricated using natural dyes extracted from krokot (Portulaca Oleracea. L). The effect of dye acidity was investigated on natural pH extract, 5.00, 4.00 and 3.00 of pH. The efficiency and stability DSSCs as a function of the dye acidity was studied. The result of the UV-Vis shows that the absorption of wave-length from dye extract of krokot is located in the visible region with the absorbance peak in 410.5 nm and 664.5 nm which are the peak of chlorophyll. The efficiency of extract krokot dye sensitized solar cells was decreasing  6.88 x 10-3 %  to  0.42 x 10-3 % when pH of the dye was adjusted from 6.27 to 3.00. DSSCs stability was also decreased look for efficiency loss from 5.27% to 97.49% in the same conditions.